Pengaruh Work Environment, Ethical Leadership, Organizational Citizenship Behavior dan Work Stress terhadap Employee Performance pada Karyawan Perusahaan Otomotif di Jakarta Timur - Harahap, Farhan Hamzah; Baliartati, Beta Oki (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aims to analyze the effect of work environment, ethical leadership, organizational citizenship behavior, and work stress on employee performance at Automotive company employees in East Jakarta. Data was collected from 178 respondents only in the marketing division and service division of Automotive companies in East Jakarta, using non-probability sampling and using purposive sampling techniques with the data collection method used was population. Data analysis used descriptive statistics by finding the average using SPSS version 25, as well as multiple regression analysis for hypothesis testing using SPSS version 25. Previously the instrument had been tested using validity and reliability tests where all statement items were valid and reliable. The research results show that the work environment has a positive effect on employee performance, ethical leadership has a positive effect on employee performance, organizational citizenship behavior has a positive effect on employee performance, and work stress has a negative effect on employee performance. Managerial implications in research, companies need to better facilitate the equipment that employees need to do their work, supervisors at Automotive companies in East Jakarta need to provide more examples of how to do things the right way in terms of ethics, companies need to tell their employees not to take time off work if they don't necessary, and companies need to provide tasks that suit employee abilities. Keywords: Employee Performance, Ethical Leadership, Organizational Citizenship Behavior , Work Environment, Work Stress.